FEASIBILITY ANALYSIS OF SUSTAINABLE CASSAVA FOOD ESTATE IN GUNUNGMAS REGENCY CENTRAL BORNEO PROVINCE - Angga Nalindo Utama; Meti Ekayani; Tatang Tiryana (SEAN Institute, 2023)
The purpose of this study is to find the availability of land conformity for the development of cassava's food estate in Gunungmas regency. Gunungmas regency is one of the location targets for the development of food estates in Indonesia . The combination of multi criteria based on hierarchical analytical process analysis and geographic information system (GIS) to produce the map of land used availability and sustainable cassava's food estate land. The Principles that used to determine of food estate suitability are the sustainability criteria of economy, social and environmental . The data used was spatial data relating, and interviews with experts regarding the weight and value to determine the extent of the interest in the hierarchy analytical process. Weighting is done on each criterion based on its level of importance on land suitability. The value of all by virtue of conformity each sub criteria . The highest value represents an area that has a high level of suitability. The weighting overlay method was used to produce a land suitability map for a sustainable cassava food estate. The results of the study show that the available land for the development of a food estate in Gunungmas Regency is 33,799.15 Ha. Sustainable cassava food estate land suitability class is 31,496.21 Ha, very suitable 496.74 Ha, class is not suitable 1,806.21 Ha.